Data on the effect of hypomyelinating leukodystrophy 6 (HLD6)-associated mutations on the TUBB4A properties - Yuki Miyamoto; Tomohiro Torii; Kazuko Kawahara; Nanami Hasegawa; Akito Tanoue; Yoichi Seki; Takako Morimoto; Megumi Funakoshi-Tago; Hiroomi Tamura; Keiichi Homma; Masahiro Yamamoto; Junji Yamauchi (Data in Brief, 2017)
Hypomyelinating leukodystrophy (HLD) is genetic demyelinating or dysmyelinating disease and is associated with at least 13 responsible genes. The mutations seem likely cause the functional deficiency of their gene products. HLD4- and HLD5-associated HSPD1 and FAM126A mutations affect biochemical properties of the gene products (Miyamoto et al. (2015,2014) [1,2]). Herein we provide the data regarding the effects of HLD6-associated tubulin beta 4A (TUBB4A) mutations on the properties.